Food related behaviors and sleep quality in university students: a descriptive study - İSLAMOĞLU, AYŞE HÜMEYRA; SABUNCULAR, GÜLEREN (My University, 2023)
Purpose: The purpose of this study was to evaluate the relationship between food addiction, night eating status and sleep quality in students studying at different faculties or departments of various universities in Turkey. Methods: A total of 1044 students from 11 different departments/faculties were included. Night Eating Questionnaire, Yale Food Addiction Scale and Pittsburgh Sleep Quality Scale were applied to the students. Also, the dietary habits (main meal and snack consumptions, the meal they skipped and the reasons, duration of meals, consumption of tea and coffee etc.) of the students were questioned. Results: Significant relationships were found between BMIs, faculties/departments, use of antidepressants, skipping breakfast status and tea/coffee consumption of students. Moreover, there were significant differences between both food addiction status (p<0.001), night eating syndrome (p<0.001) and sleep quality. Students with poor sleep quality had more frequent night eating behavior and food selectivity. Conclusion: These findings suggest that for managing students’ eating problems like night eating and food addiction, their sleep quality should be improved, and vice versa.

Amaç: Bu çalışmanın amacı, Türkiye’deki çeşitli üniversitelerin farklı fakülte veya bölümlerinde okuyan öğrencilerde gıda bağımlılığı, gece yeme durumu ve uyku kalitesi arasındaki ilişkiyi değerlendirmektir. Yöntem: Çalışmaya 11 farklı bölüm/fakülteden toplam 1044 öğrenci dahil edildi. Öğrencilere Gece Yeme Anketi, Yale Gıda Bağımlılığı Ölçeği ve Pittsburgh Uyku Kalitesi Ölçeği uygulandı. Ayrıca öğrencilerin beslenme alışkanlıkları (ana öğün ve ara öğün tüketimleri, atladıkları öğün ve nedenleri, öğün süreleri, çay/kahve tüketimleri vb.) sorgulanmıştır. Bulgular: Öğrencilerin BKİ’leri, fakülte/bölümleri, antidepresan kullanımı, kahvaltıyı atlama durumu ve çay/kahve tüketimi arasında anlamlı ilişkiler bulunmuştur. Ayrıca, hem gıda bağımlılık durumu (p<0.001) hem de gece yeme sendromu (p<0.001) ile uyku kalitesi arasında anlamlı fark saptanmıştır. Düşük uyku kalitesine sahip öğrenciler, daha sık gece yeme davranışına ve besin seçiciliğine sahip bulunmuştur. Sonuç: Bu bulgular, öğrencilerin gece yeme ve gıda bağımlılığı gibi yeme problemlerini yönetmek için uyku kalitelerinin iyileştirilmesi gerektiğini ve bunun tersinin de geçerli olduğunu göstermektedir.
Üniversite öğrencilerinde besin ilişkili davranışlar ve uyku kalitesi: Tanımlayıcı bir çalışma
Keywords: Sleep quality; Food addiction; Night eating syndrome; University students; Uyku kalitesi; Gıda bağımlılığı; Gece yeme sendromu; Üniversite öğrencileri